Screening of hypothyroidism disorder in newborns by heel prick level of thyroid-stimulating hormones. - Rashid, Shaista; Nadeem, Shabnam; Naseeb, Shazia (International Journal of Endorsing Health Science Research, 2021)
Background: Thyroid hormones are vital for fetal development and regulation of neuropsychological function. Therefore an adequate amount of thyroid hormone levels are necessary for brain development cognitive function. Newborn screening for congenital hypothyroidism is a great achievement in preventive medicine. Screening for hypothyroidism disorder using heel prick samples is considered essential for preventing intellectual dysfunction and delayed growth. The objective of the present study was to determine the frequency of hypothyroidism disorder in newborns. Methodology: A cross-sectional study was conducted at Abbasi Shaheed Hospital, Gynae & Obstetrics Department, Karachi, Pakistan. Blood samples were obtained from 257 neonates between 3rd & 5th day after birth by the heel prick method. Babies of Mothers having thyroid diseases were excluded from the study. Serum Thyroid-stimulating hormones (TSH) were tested using the enzyme-linked immunosorbent assay method. Newborn serum TSH > 20 miu/L was considered abnormal. Results: The overall mean age of neonates was 3.47 ± 0.57 days. Out of the total 257 neonates screened, female babies had higher TSH levels and congenital hypothyroidism was found in 4(1.55%) cases. The observed mean TSH level was 4.09 ± 0.24 mIU/L. Conclusion: In conclusion, the observed frequency of neonatal hypothyroidism in this single-center study prompts the need for early screening and diagnosis. The screening should be included in the post-natal period to prevent sequels associated with hypothyroidism for timely diagnosis and treatment of newborns.